Mechanism of carbon nanotube growth in expanded graphite via catalytic pyrolysis reaction using carbores P as a carbon source - Wang, Yilong; Zhang, Wenli; Chen, Yuejun; Zeng, Xiongfeng; Huang, Jiankun; Wei, Hengyong; Tu, Junbo (Frontiers in Chemistry, 2023)
Carbon nanotubes (CNTs) had potential applications in energy conversion and storage devices, and it could be prepared by expanded graphite loaded with catalyst at high temperature, however, the mechanism of carbon nanotube growth in expanded graphite need further confirmation. In this work, carbon nanotubes’ in situ growth in expanded graphite (EG) were prepared via catalytic pyrolysis reaction using carbores P as a carbon source and Co(NO3)3•6H2O as a catalyst. The results of X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray spectroscope (EDS) indicated the carbon nanotubes could generate in, EG with the presence of carbores P as a carbon source and cobalt nitrate as a catalyst. More interestingly, the growth mechanism of carbon nanotubes could be concluded by the results of differential thermal analysis-thermogravimetry-mass spectrometry (DTA-TG-MS) and X-ray photoelectron spectroscopy (XPS) analysis. The pyrolysis products of carbores P were mainly hydrocarbon gas such as CH4 gas, which reacts with Co(NO3)3·6H2O catalyst to reduces CoOx to Co particles, then the carbon form pyrolysis was deposited the on the surface catalyst Co particles and, after continuous solid dissolution and precipitation, carbon nanotubes were at last generated in EG at last.